Single nanosheet can sustainably generate oxygen and inhibit respiration simultaneously in cancer cells. Issue 2 (9th December 2020) - Huang, Wei-Qiang; Wang, Fei; Shen, Ai-Zong; Zhang, Lei; Nie, Xuan; Zhang, Ze; Chen, Guang; Xia, Lei; Wang, Long-Hai; Ding, Sheng-Gang; Meng, Qing-Yong; Zhang, Wen-Jian; et al.
Abstract : Ti2 C(OH)2 can relieve the hypoxia in tumors via generating O2 from endogenous H2 O2 and inhibiting mitochondrial respiratory in cancer cell. Abstract : In a tumor, the abnormal cancer cell proliferation results in an insufficient O2 supply, and meanwhile cancer cells consume O2 very fast. The imbalance between a low oxygen supply and overwhelming oxygen consumption results in a low oxygen concentration in solid tumors. Therefore, in order to relieve hypoxia in tumors, it is necessary to not only sustainably generate O2, but also inhibit mitochondrial respiration simultaneously. Here, we found that a single Ti2 C(OH)2 nanomaterial not only can sustainably generate O2 but also simultaneously highly inhibits mitochondrial respiration via binding phosphorylation proteins onto the surface in cancer cells. Ce6 was linked onto Ti2 C(OH)2, forming Ti2 C(OH)2 –Ce6. Ti2 C(OH)2 –Ce6 could highly relieve hypoxia in tumors via the combination of sustainable O2 generation and respiration inhibition, produce enough 1 O2 to kill cancer cells via PDT, and also effectively convert the absorbed light energy into thermal energy to kill cancer cell via PTT, thereby highly enhancing the cancer therapy.